Indoor-outdoor air quality interrelation at museum environments: The case of the Museum of Geoastrophysics at N.O.A - Δρούγκα, Φανή (Πανεπιστήμιο Πελοποννήσου, 2017)
Nowadays, the problem of Indoor Air Quality (IAQ) has received crucial concern regarding the cultural heritage deterioration. The natural decay of materials and artworks exposed to non-controlled environmental conditions of temperature and relative humidity or exposed to gaseous and airborne particulate pollutants, either emitted indoors or penetrating from the outdoor environment, could be accelerated. As a result, monitoring and controlling the indoor microclimatic conditions (temperature and relative humidity) and the level of indoor pollution is of major importance for the applied conservation and preservation techniques of cultural heritage. The present study focuses on the measurements of airborne particulates and gaseous pollutants (NO, NO2, SO2, CO, O3 and PM10 and determination of their content in OC, EC and ions), as well as the thermo hydrometric conditions indoors and outdoors of the Library of the Museum of the Geoastrophysics of the National Observatory of Athens which hosts books from the 16th century. The scope of the thesis is to measure, evaluate and define the threats of the existing pollutants, temperature and relative humidity for the materials met indoor. To evaluate the air quality inside the museum a monitoring campaign was performed during summer-time period from 4 to 31/8/16. The experimental period was separated into 3 different periods. The background days where there was a monitoring of the library indoor according to the usual conditions, the air condition days where the air was conditioned for 8 hours and the ventilation days where natural ventilation took place for two hours a day (morning and midday). The Library was exposed to gaseous pollutants and the microclimate conditions, temperature and relative humidity, proved to be the most crucial threats for the book collection. Temperature and relative humidity indicated that for the study period the measured levels were out of the recommended limit values, presenting also a wide range of fluctuations. This could possibly pose impact on books in long term basis, leading to possible cracking of the paper, breaking of the fibers, damage by embrittlement and warping of the cover. Furthermore, pollutants such as SO2, NOx and O3 presented to be higher than the acceptable limits, which can also lead to embrittlement and discolorance of the paper and weakening or powdered surface to the leather covers of books. To sum up, given that the cultural value of those exhibits is huge and their sensitiveness to environmental conditions is quite high, extensive monitoring for longer period and evaluation of the findings is suggested in order to obtain an integrated knowledge of the possible threats under extreme weather conditions (cold or heat waves) that seem to influence the indoor air quality of the Library.
Keywords: Μουσείο Γεωαστροφυσικής του Εθνικού Αστεροσκοπείου Αθηνών; Εσωτερική ατμοσφαιρική μόλυνση -- Μέτρηση; Εξωτερική ατμοσφαιρική μόλυνση -- Μέτρηση; Μέθοδοι συντήρησης μουσείων; Διαχείριση ποιότητας του αέρα; Κτήρια μουσείων -- Μηχανική περιβάλλοντος; Μνημεία -- Συντήρηση και αποκατάσταση -- Ελλάδα; Υλικό βιβλιοθήκης -- Συντήρηση και αποκατάσταση-- Ελλάδα; Αντικείμενα τέχνης -- Προστασία; Μουσείο Γεωαστροφυσικής του Εθνικού Αστεροσκοπείου Αθηνών; Εσωτερική ατμοσφαιρική μόλυνση; Εξωτερική ατμοσφαιρική μόλυνση; Ποιότητα αέρα